2012
DOI: 10.1080/07418825.2012.677466
|View full text |Cite
|
Sign up to set email alerts
|

Does a Rising Tide Lift All Boats? Labor Market Changes and Their Effects on the Recidivism of Released Prisoners

Abstract: The dramatic growth in incarceration nationally has increased attention to the factors that influence recidivism among ex-prisoners. Accordingly, scholars have called for research that identifies factors, such as employment opportunities, that may influence reentry experiences. Few studies, however, have examined how changes in labor market conditions affect ex-prisoner offending. Drawing on prior scholarship, this study examines the effect of such changes on the recidivism of ex-prisoners and, in particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 81 publications
(137 reference statements)
1
8
0
Order By: Relevance
“…Provisions of instrumental as well as expressive social supports such as clinical interventions and rehabilitative programs may also enhance inmates’ willingness to recognize the legitimacy of authority figures inside prisons. These findings are consistent with prior studies of visitation, rehabilitation, and job programs on future offending (Cullen & Jonson, 2012; Duwe & Clark, 2013; Mears et al, 2012; Mears, Wang, & Bales, 2014; Wilson, Bouffard, & MacKenzie, 2005).…”
Section: Resultssupporting
confidence: 90%
“…Provisions of instrumental as well as expressive social supports such as clinical interventions and rehabilitative programs may also enhance inmates’ willingness to recognize the legitimacy of authority figures inside prisons. These findings are consistent with prior studies of visitation, rehabilitation, and job programs on future offending (Cullen & Jonson, 2012; Duwe & Clark, 2013; Mears et al, 2012; Mears, Wang, & Bales, 2014; Wilson, Bouffard, & MacKenzie, 2005).…”
Section: Resultssupporting
confidence: 90%
“…In keeping with this research, we use race- and ethnicity-specific measures and models to test for potential interactional effects of distance and context on social support access. This approach accords with research on racial and ethnic stratification that highlights the marked differences in the social contexts of racial and ethnic groups (Krivo and Peterson 2000; see also, Alba, Logan, and Bellair 1994; Mears et al 2014; Western 2006). For each index, we used four measures from the 2000 U.S. Census: percentage of female-headed households, percentage below the poverty line, percentage without a high school diploma, and median household income.…”
Section: This Studymentioning
confidence: 83%
“…The potential consequences of adversely affecting visitation go beyond inmate concerns about maintaining contact with family. Many studies have found that visitation is associated with inmate behavior and the chances of successful integration upon release (Duwe and Clark 2013; Lanier 1993; LeBel and Maruna 2012; Mears, Wang, and Bales 2014; Rose and Clear 2003; Wolff and Draine 2004). Visitation may reduce strain and increase social bonds, for example, and in turn reduce misconduct and recidivism and improve other reentry outcomes (Christian et al 2006; Drago et al 2011; Liebling 1999; Cochran 2012; Listwan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 35 years after the DoJ study, and despite increasing levels of methodological sophistication, meaningful variation in the operationalization of recidivism persists. A recent Campbell Collaboration report concludes that among studies of custodial sanctions, reconvictions and rearrests are the most commonly reported recidivism operationalizations within the corrections literature (Killias, Villettaz, and Zoder 2006; Mears, Wang, and Bales 2014), though many others are in active use. The scope of definitions that are used, and how different definitions impact conclusions, is also evident in the most recent multistate Bureau of Justice Statistics (BJS) study of post-release recidivism (Durose et al 2014).…”
Section: Operationalizing Recidivismmentioning
confidence: 99%